Screening of selected Zingiberaceae extracts for dengue-2 virus protease inhibitory activities - Tan, Siew Kiat *; Pippen, Richard; Rohana Yusof,; Noorsaadah Abd Rahman,; Halijah Ibrahim,; Norzulaani Khalid, (Sunway University College, 2006)
The crude extracts and the methanol and hexane partitioned fractions from the rhizomes of six Zingiberaceae comprising five Curcumas and one Zingiber were screened for dengue-2 (Den2) virus NS2B?NS3 protease inhibition. The percentage inhibition of Den2 virus NS2B?NS3 protease cleavage of the substrate showed linear dose-dependent increment for all the samples tested. The crude extracts were less potent than the best of the partitioned fractions. For all three concentrations studied, the methanol fractions of the extracts of Curcuma longa (L.) (CL), Zingiber zerumbet Smith (ZZ) and Curcuma rubescen Roxb. (CR) were much more inhibiting than the corresponding hexane fractions but the converse was true for Curcuma aeroginosa Roxb. (CA). However, the inhibiting activities of the two partitioned fractions of the extracts of Curcuma mangga Roxb. (CM) and Curcuma xanthorhiza Roxb. (CX) were found to be similar. The CL methanol fraction exhibited the strongest inhibitory activity (91.3±3.1%, 300 ppm), followed closely by methanol fraction of ZZ (89.0±1.7%, 300 ppm). The results show that the methanol fractions of CL and ZZ, and both the methanol and hexane fractions of CM were most potent against Den2 virus NS2B?NS3 protease activity and may provide potential leads towards the development of anti-viral agents.